Improving Computational Thinking & Creative Problem Solving: ESD & Micro:bit for Climate - Umam, Ahmad Naufal; Herlina, Kartini; Abdurrahman, Abdurrahman; Ertikanto, Chandra (Journal of Natural Science and Integration, 2024)
This study aims to validate the Student Worksheet titled "ESD-Climate Change," developed using the Understanding by Design approach and complemented by Micro:bit devices. The validation was conducted by three experts, including two academic experts in education and one distinguished educator. Main findings from this study is the validation results reveal that this worksheet adheres to high standards. The "Content" dimension achieved a score of 84.33%, labeled "Very Suitable," signifying its strong relevance to climate change-related learning objectives. The "Construct" dimension garnered a score of 79.17%, categorized as "Suitable," indicating potential for improvement in some construction aspects. The "Language" dimension received an impressive score of 85.90%, also labeled "Very Suitable," highlighting its excellent language quality and communication proficiency. Finally, the "Design" dimension received the highest score of 95.18%, categorized as "Very Suitable," affirming the worksheet's strong design, encompassing its cover and content presentation. Overall, these findings underscore the worksheet's high quality in terms of content, language, and design, with minimal room for improvement in the construction aspect. This study contributes to the development of technology and environment-centered educational materials, which are increasingly pertinent in addressing future challenges associated with climate change.Keywords: ESD, computational thinking, creative problem solving